A review of the ground spider genus Trichothyse Tucker, 1923 (Araneae, Gnaphosidae) - Sankaran, Pradeep M.; Haddad, Charles R.; Tripathi, Rishikesh (Zootaxa, 2025)
The genus Trichothyse Tucker, 1923 is presently represented by four southern African species, T. africana (Tucker, 1923), T. hortensis Tucker, 1923 and T. subtropica Lawrence, 1927, known only from their females, and T. fontensis Lawrence, 1928, known only from the male. In this paper, the genus is reviewed and the latter three species are redescribed. The previously unknown female of T. fontensis is described for the first time. The female of Xerophaeus zuluensis Lawrence, 1938 is redescribed, its previously unknown male is described for the first time, and the species is hereby transferred to Trichothyse as T. zuluensis (Lawrence, 1938) comb. nov. A new species known from both sexes, T. karoo Haddad & Sankaran sp. nov., is described from South Africa, and the hitherto unknown male of T. jodhpurensis (Gajbe, 1993) comb. nov. is described for the first time, together with a redescription of its female. Eleven species and one subspecies are transferred from Poecilochroa Westring, 1874 sensu lato to Trichothyse, two of which are of African distribution [T. antineae (Fage, 1929) comb. nov. and T. pugnax (O. Pickard-Cambridge, 1874) comb. nov.], nine that are distributed in the Palaearctic Region [T. furcata (Simon, 1914) comb. nov., T. golan (Levy, 1999) comb. nov., T. hamipalpis (Kroneberg, 1875) comb. nov., T. ilkerakkusi (Coşar, Danişman & Marusik, 2024) comb. nov., T. jodhpurensis comb. nov., T. loricata (Kritscher, 1996) comb. nov., T. perversa (Simon, 1914) comb. nov., T. poonaensis (Tikader, 1982) comb. nov. and T. senilis auspex (Simon, 1878) comb. nov.], and one that has an extended distribution in both the Palaearctic Region and Africa [T. senilis (O. Pickard-Cambridge, 1872) comb. nov.].